1997
DOI: 10.1038/sj.onc.1200951
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D2 activates Cdk2 in preference to Cdk4 in human breast epithelial cells

Abstract: To investigate the possibility of diering roles for cyclins D1 and D2 in breast epithelial cells, we examined the expression, cell cycle regulation and activity of these two G 1 cyclins in both 184 normal breast epithelial cells and T-47D breast cancer cells. Synchronisation studies in 184 cells demonstrated that cyclin D1 and cyclin D2 were dierentially regulated during G 1 , with cyclin D2 abundance increasing by 3.7-fold but only small changes in cyclin D1 abundance observed. The functional consequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 37 publications
8
33
0
2
Order By: Relevance
“…Although cyclins are generally considered as positive mediators of mitogen-induced cell cycle progression, it has been shown that loss of CCND2 expression occurs in primary breast tumours (Evron et al, 2001). Despite this, expression of CCND2 can reduce the dependence on serum for proliferation of breast epithelial cells, and promote cell cycle progression through activation of cdk2 (Sweeney et al, 1997). Thus, a combination of factors appears to drive ErbB-2-dependent cell cycle progression and hence tumorigenic potential in ErbB-2-overexpressing luminal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although cyclins are generally considered as positive mediators of mitogen-induced cell cycle progression, it has been shown that loss of CCND2 expression occurs in primary breast tumours (Evron et al, 2001). Despite this, expression of CCND2 can reduce the dependence on serum for proliferation of breast epithelial cells, and promote cell cycle progression through activation of cdk2 (Sweeney et al, 1997). Thus, a combination of factors appears to drive ErbB-2-dependent cell cycle progression and hence tumorigenic potential in ErbB-2-overexpressing luminal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Densitometric analysis of autoradiographs was performed using a Molecular Dynamics (Sunnyvale, CA) Personal Densitometer SL and IP LabGel analysis software (Signal Analytics, VA). Quantitation of protein levels by this method was linear over the range of intensities measured see also Sweeney et al, 1997). Relationships between expression levels were determined by simple regression analysis using the software program StatView SE+Graphics (Abacus Concept Inc.).…”
Section: Western Blot Analysis Immunoprecipitation and Kinase Assaysmentioning
confidence: 99%
“…51 Interestingly, Cyclin D2 seems to have a unique preference for CDK binding among the D-type cyclin family. 52 Unlike Cyclin D1, Cyclin D2 can preferentially bind to CDK2 under some cellular contexts. Although it has not been tested, Cyclin D2/CDK2 might be relatively insensitive to the control by CDC25A.…”
mentioning
confidence: 99%